Adjuvant effects of Lactobacillus casei added to a renutrition diet in a malnourished mouse model - Gauffin Cano, María Paola (2002)
Nutritional deficiencies are associated with impaired immune response, affecting the body’s defence mechanisms. It is also known that Lactic Acid Bacteria (LAB) and fermented products such us yogurt have immunopotentiator activity and nutritional properties, and could thus be used as a valuable supplement in a renutrition diet. The aim of this study was to determine, in a non-severe malnutrition model, the effective dose of Lactobacillus casei (L.casei), which when is used as an adjuvant in a renutrition diet, would modulate the mucosal immune system and induce recovery of the integrity of the intestinal barrier. The experiments were performed on groups of malnourished and renourished BALB/c mice. They received after milk renutrition a supplement of different doses and periods of L. casei feeding. We measured body weight; hematologic values and serum proteins. We also characterized small intestine immunoglobulin secreting cells, intraepithelial leukocytes, mastocytes and goblet cells. Structural and ultrastructural studies were performed. Our results suggest that impaired gut barrier and mucosal immune function produced by malnutrition can be reversed by L. casei and that the dose of 107 cfu/day/mouse administered during 5 consecutive days was the optimal one for recovery of the gut mucosal immune system. The clinical significance of these findings suggests ways for improving mucosal immunity, and generating protection against enteropathogens in hosts immunosuppressed by malnutrition.